2018
DOI: 10.1186/s12885-018-4462-y
|View full text |Cite
|
Sign up to set email alerts
|

γ-Tocotrienol induces apoptosis in pancreatic cancer cells by upregulation of ceramide synthesis and modulation of sphingolipid transport

Abstract: BackgroundCeramide synthesis and metabolism is a promising target in cancer drug development. γ-tocotrienol (GT3), a member of the vitamin E family, orchestrates multiple effects that ensure the induction of apoptosis in both, wild-type and RAS-mutated pancreatic cancer cells. Here, we investigated whether these effects involve changes in ceramide synthesis and transport.MethodsThe effects of GT3 on the synthesis of ceramide via the de novo pathway, and the hydrolysis of sphingomyelin were analyzed by the expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 54 publications
1
13
0
Order By: Relevance
“…ASM catalyzes the hydrolysis of sphingomyelin to produce ceramide. Here, according to the methods described by Li et al [ 11 ], Palau et al [ 13 ] and Maroni et al [ 20 ], RAECs were incubated with an anti-ceramide antibody followed by goat anti-mouse IgG-FITC. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ASM catalyzes the hydrolysis of sphingomyelin to produce ceramide. Here, according to the methods described by Li et al [ 11 ], Palau et al [ 13 ] and Maroni et al [ 20 ], RAECs were incubated with an anti-ceramide antibody followed by goat anti-mouse IgG-FITC. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Immunofluorescence of ceramide was measured according to the methods described by Li et al [ 11 ] and Palau et al [ 13 ]. RAECs were plated in a six-well plate.…”
Section: Methodsmentioning
confidence: 99%
“…RE also contains small amounts of FA and T3, which are known to have anti-cancer and anti-inflammatory properties Table 1 19,20 . It was recently, reported that T3 controls the synthesis and metabolism of intrinsic sphingolipids, including GlcCer, in the colon and pancreatic cancer cells in vitro 23,24 . Additionally, when both T3 and free FA are added to the colon and pancreatic cancer cells in vitro, intracellular T3 concentrations are higher than when T3 is added alone 25,26 .…”
Section: Discussionmentioning
confidence: 99%
“…Hence, targeting cell cycle checkpoints can be an important strategy for cancer therapy [61]. Recent scientific evidence has documented the potential role of tocotrienols as therapeutic agents in cancer treatment through the modulation of cell cycle proteins in pancreatic cancer [62,63], leukemia [64,65], glioblastoma [66], gastric cancer [67], neuroblastoma [68] etc. In another study, Abubakar et al, (2017) documented the anti-proliferative potency of γ-T3 and jerantinine A in brain cancer (U87MG) cells, and found that the combination can lead to G0/G1 cell cycle arrest and trigger disruption of microtubule networks, thus promoting Fas and p53 induced apoptosis mediated through the death receptor and mitochondrial pathways (Figure 3) [69].…”
Section: Major Anti-cancer Functions Of Tocotrienolsmentioning
confidence: 99%